Optimal Control for a Gantry Crane System Using Priority Fitness Strategy of Particle Swarm Optimization - Farrez Irsyad Md Noor; Hazriq Izzuan Jaafar; Rozaimi Ghazali; Herman Wahid; Liyana Ramli (: Association for Scientific Computing Electronics and Engineering (ASCEE), 2026)
Non-Indexed Publication